Accurate Bond Lengths to Hydrogen Atoms from Single‐Crystal X‐ray Diffraction by Including Estimated Hydrogen ADPs and Comparison to Neutron and QM/MM Benchmarks. Issue 19 (15th March 2017) - Dittrich, Birger; Lübben, Jens; Mebs, Stefan; Wagner, Armin; Luger, Peter; Flaig, Ralf
Abstract: Amino acid structures are an ideal test set for method‐development studies in crystallography. High‐resolution X‐ray diffraction data for eight previously studied genetically encoding amino acids are provided, complemented by a non‐standard amino acid. Structures were re‐investigated to study a widely applicable treatment that permits accurate X−H bond lengths to hydrogen atoms to be obtained: this treatment combines refinement of positional hydrogen‐atom parameters with aspherical scattering factors with constrained "TLS+INV" estimated hydrogen anisotropic displacement parameters (H‐ADPs). Tabulated invariom scattering factors allow rapid modeling without further computations, and unconstrained Hirshfeld atom refinement provides a computationally demanding alternative when database entries are missing. Both should incorporate estimated H‐ADPs, as free refinement frequently leads to over‐parameterization and non‐positive definite H‐ADPs irrespective of the aspherical scattering model used. Using estimated H‐ADPs, both methods yield accurate and precise X−H distances in best quantitative agreement with neutron diffraction data (available for five of the test‐set molecules). This work thus solves the last remaining problem to obtain such results more frequently. Density functional theoretical QM/MM computations are able to play the role of an alternative benchmark to neutron diffraction. Abstract : Accurate X−H distances to hydrogen atoms can efficiently be obtained by density functional theory QM/MM computations, as an alternative to neutron diffraction. High‐resolution X‐ray diffraction data for eight genetically encoding amino acids and a non‐standard amino acid were re‐investigated. Best X−H interatomic distances from X‐ray diffraction in quantitative agreement with the above‐mentioned methods were refined in the presence of estimated H‐ADPs.